2016
DOI: 10.1155/2016/9843019
|View full text |Cite
|
Sign up to set email alerts
|

Micro/Nanostructure and Tribological Characteristics of Pressureless Sintered Carbon Nanotubes Reinforced Aluminium Matrix Composites

Abstract: This study reports the manufacture, microstructure, and tribological behaviour of carbon nanotube reinforced aluminium composites against pure aluminium. The specimens were fabricated using powder metallurgy method. The nanotubes in weight percentages of 0.5, 1.0, 1.5, and 2.0 were homogeneously dispersed and mechanically alloyed using a high energy ball milling. The milled powders were cold compacted and then isothermally sintered in air. The density of all samples was measured using Archimedes method and all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…With 1 wt.% CNT content, the relative density of H1 (93.5 %) is lower in comparison with that of composite without Cu (94.6%), but microhardness of specimen H1 is nearly 2.3 times higher. The decrease in microhardness when CNT content higher 1.5 % could be due to the porosity formed by CNT clusters as evidenced by many authors [7,18,[26][27][28]. In conclusion, the high microhardness of CNT/Al-Cu composite is due to the synergistic effect of CNTs reinforcement and precipitation hardening of Al-Cu matrix and also affected by the defect and uniform dispersion of CNTs during the preparation process.…”
Section: Resultsmentioning
confidence: 70%
“…With 1 wt.% CNT content, the relative density of H1 (93.5 %) is lower in comparison with that of composite without Cu (94.6%), but microhardness of specimen H1 is nearly 2.3 times higher. The decrease in microhardness when CNT content higher 1.5 % could be due to the porosity formed by CNT clusters as evidenced by many authors [7,18,[26][27][28]. In conclusion, the high microhardness of CNT/Al-Cu composite is due to the synergistic effect of CNTs reinforcement and precipitation hardening of Al-Cu matrix and also affected by the defect and uniform dispersion of CNTs during the preparation process.…”
Section: Resultsmentioning
confidence: 70%
“…Other technological additions are stearic acid (1 wt.%) and a mixture of CaCl 2 , NaCl, and KCl in the ratio 2:1: (3 wt.%). Metal-matrix composites containing carbon nanostructures, due to their high hardness and self-lubrication effect, can be considered as a promising solution to provide better wear resistance [4][5][6][7][8][9][10]. It was noted in [4] that in composites, carbon nanotubes prevented the direct contact of two sliding surfaces due to the formation of lubricating film and showed better wear resistance compared to other dispersed particles.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of 4% carbon nanotubes leads to a decrease in the friction coefficient by 55%. In [5], it was found that CNT-reinforced composites showed a lower wear rate and friction coefficient compared to pure aluminum under soft wear conditions. However, under hard wear conditions these composites showed a higher coefficient of friction and wear rate compared to pure aluminum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composites with nanotubes as a reinforcing phase are usually manufactured by methods of thermal spraying, sintering, powder metallurgy, spark plasma extrusion, and spark plasma sintering. Due to mechanical alloying in the manufacture of the composite, it was possible to achieve a uniform distribution of CNT in the metal matrix [10,11]. It is known that the degree of uniformity of the CNT distribution in a metal matrix is one of the key factors that affect the resulting physicalmechanical properties of the composite [10].…”
Section: Introductionmentioning
confidence: 99%